The Use of Simile in Charlotte Bronte’s Jane Eyre - Yuniar Fatmasari; Nikhla Khotmalinda (Metaphor, 2021)
In literary works, the use of beautiful language is used by the author as efforts to enrich the impression, and expand the imagination of the readers. Sometimes, readers often encounter difficulties in understanding the meaning of those unliteral words. One of the keys to understanding the meaning of words is to understand figurative language. Knowing figurative language especially similes can make us able to understand the implicit or explicit meaning of literary works. In this study, the writers analyze the simile used in Bronte’s Jane Eyre. This qualitative study focuses on the simile type human, treats, and feelings as formulated by Reimer (2018). Reading the novel and labeling the data is the method of data collection then describing the data based on its semantic meaning is the method of data analysis. The research's results show that there are 29 utterances belong to similes type human treats, people, and feelings.